Investigation of solidification behaviour of Mg–6Al and Mg–9Al alloys using in situ neutron diffraction. (January 2015) - Elsayed, A.; Sediako, D.; Ravindran, C.
Abstract : In situ neutron diffraction was used to examine the solidification behaviour of Mg–6 wt-%Al and Mg–9 wt-%Al alloys. Samples of each Mg–Al alloy were heated above their liquidus temperatures and stepwise cooled to 420°C while simultaneously collecting neutron scattering intensities. The solidified alloys were examined using scanning electron microscopy. Mainly blocky Mg17 Al12 was found in Mg–6 wt-%Al alloy while branched Mg17 Al12 adjacent to a large network of fine lamellar Mg17 Al12 was found in the Mg–9 wt-%Al alloy. The neutron diffraction data accurately described the fraction solid growth as represented by the ( ) crystallographic plane over the entire solidification regime. The fraction solid of the Mg–6 wt-%Al alloy rose quickly at temperatures just below the liquidus point and rapidly approached 100% until solidification was complete while the Mg–9 wt-%Al alloy showed a more linear transition from liquid to solid. Neutron diffraction was also capable of detecting the formation of eutectic Mg17 Al12 in the Mg–9 wt-%Al alloy. This research demonstrates unique possibilities in using neutron diffraction for further understanding of nucleation, eutectic formation and solid phase evolution of Mg alloys.